Realization Of Entrepreneurial Values Towards Students' Understanding During Learning In Higher Education - Adiansyah, Adi; Isnawati, Isnawati; Dahlena, Alni; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
Abstract – In Garut Regency, there are very few MSMEs that are classified as medium and large businesses, even in the small category, the number is still very minimal. The majority of MSMEs in Garut Regency are still classified as micro businesses (very small). This study aims to describe how prospective entrepreneurs or existing entrepreneurs start and grow their businesses, especially for students in Garut Regency who study entrepreneurship. This study uses a Qualitative approach, which uses the literature review method, it is expected to be able to provide an overview of what students need to pay attention to in building a competitive business. The results of this study identified that students with high motivation tend to show better results in entrepreneurship learning, from the results of the publish or perish and vosviewer analysis it was analyzed that the nodes regarding student understanding through the realization of entrepreneurial values in learning in Higher Education must implement learning based on entrepreneurial values, so that students are able to develop their abilities and have critical thinking and have high creativity. Therefore, students who are involved in practical activities will tend to have a better understanding and greater interest in entrepreneurship. Keywords: entrepreneurial values, understanding of learning, higher education.